Bradyrhizobium strains in symbiosis with dwarf pigeon pea under greenhouse and field conditions - Rufini, Márcia; Oliveira, Dâmiany de Pádua; Trochmann, André; Soares, Bruno Lima; Andrade, Messias José Bastos de; Moreira, Fatima Maria de Souza (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the symbiotic efficiency of nitrogen‑fixing bacterial strains, from the genus Bradyrhizobium, with dwarf pigeon pea. The experiments were carried out in Leonard jars, in pots with soil and in the field. In Leonard jars, 11 strains were tested, and the most effective in promoting pigeon pea growth were evaluated in pots with soil (Oxisol and Cambisol) and in the field (Oxisol). In all experiments, treatments were compared to two positive controls (strains approved as inoculants for pigeon pea cultivars, BR 2003 and BR 2801) and to two controls without inoculation, one with a high concentration of mineral N, and the other, depending on the experiment, without mineral N (soil) or with low N concentration (Leonard jars). Some strains have provided plant growth similar or superior to the reference strains and to the controls in Leonard jars. In the pot experiment with soil, the soil type influenced the treatments. In the field, there was no difference among treatments, and the native strains promoted a good plant growth. Dwarf pigeon pea is able to establish a symbiotic association with nitrogen‑fixing bacteria, and the strain UFLA 03‑320 has the potential to be recommended for this crop together with the BR 2801 strain.